Legal Certainty for the Fena Customary Law Community Following the Establishment of South Buru Regency (A Study of Buru Regency and South Buru Regency) - Mangemba, Toufik; Salmon, Hendrik; Bakarbessy , A.D. (Indonesian Journal of Multidisciplinary Science, 2026)
This study examines the issue of legal certainty for the Fena customary law community following the establishment of South Buru Regency in Indonesia. The background of this research is rooted in the mismatch between historically formed customary territories, particularly Regenschaap and Fena, and newly defined administrative boundaries resulting from regional expansion policies. This discrepancy has created legal ambiguity regarding the recognition, authority, and governance of customary institutions. The objective of this research is to analyze the extent to which legal certainty is affected and to propose solutions for harmonizing customary and administrative systems. The study employs a normative legal research method, utilizing primary legal materials such as the 1945 Constitution and statutory regulations, as well as secondary sources including legal literature and scholarly works. Data are collected through document analysis and interpreted using qualitative normative approaches. The results reveal that inconsistencies between customary structures and administrative jurisdictions lead to overlapping authority, unclear leadership legitimacy, and potential conflicts in governance. The discussion highlights the need for formal recognition of Regenschaap, clear mapping of customary territories, and inter-regional coordination mechanisms. In conclusion, strengthening legal certainty requires integrating customary law systems into formal legal frameworks while preserving their sociocultural legitimacy.